Analysis of energy, economy, and carbon emission of nested cascade refrigeration cycle with heat recovery system. (April 2022) - Hu, Rui; Liu, Xinyu; Zhang, Xuelai; Yang, Luwei
Highlights: The recovery temperature of condensation heat is increased. In economic analysis, the impact of the latest policy is taken into consideration. It is a reference for China's "carbon peak, carbon neutralization" policy. Abstract: Condensation heat recovery is a way to save energy and reduce carbon emissions. For the auto-cascade refrigeration cycle system, increasing the heat recovery temperature is contradictory to ensuring the refrigerate performance of the system. Here is a nested cascade refrigeration cycle system with a heat recovery system is designed to increase the heat recovery temperature. Carry out energy, economy, and carbon emissions analysis of the system. In the economic analysis, the impact of carbon tax trading policies was considered. The analysis results show that when cooling 1 kgR23 consumes the same energy and obtains the same heat supply when the recovery temperature of the auto-cascade refrigeration cycle reaches 50°C, the recovery temperature of the heat recovery system is 67°C, which increases the recovery temperature by 17 °C. Without considering carbon tax transactions, when the recovery temperature is lower than 100 °C, the economy of the heat recovery system is better than that of standard coal; and when the recovery temperature is higher than 100 °C, the economy of standard coal is better. When considering the impact of carbon tax transactions, when the heat recovery temperature is below 110 °C, and the heat recovery system is the most economical. Among them, when the condensation temperature of R744 rises from 50 °C to 120 °C in the heat recovery system, the carbon dioxide emissions increase from 20.8 kg/GJ to 45.84 kg/GJ. In the temperature range of 50– 120 °C, it is lower than electric heating, standard coal heating, and natural gas heating.